Effect of functional balance training on dynamic postural control in those who wear high-heeled shoes. - Toiem, K.; Phonsrithi, C.; Boonchuay, N.; Nacharoen, P.; Tantarawongsa, P.; Somthavil, S.; Boonyarom, O.; Srisupornkornkool , K. (Chulalongkorn Medical Journal, 2023)
Background : High-heeled shoes are still among the favorite footwear choices and necessary in some professions because of their elegance. However, wearing high heels for a long time causes discomfort and problems with the musculoskeletal system. Therefore, it is important for those who wear high-heeled shoes to exercise by doing ankle exercises and balance training that focus on the functional balance required for activities in daily life. Objective : To study the effect of functional balance training on dynamic postural control among those who wear high-heeled shoes. Methods : Nineteen participants (three of the original 22 participants were excluded), who were aged 18 to 25 years old; they were divided into control group (CG) (n = 9) and functional balance training group (FBTG) (n = 10) that received functional balance training for four weeks. Modified Star Excursion Balance Test was used to study the effect of dynamic postural control and the wireless muscle strength tester was used to measure the strength of the ankle muscles at four weeks. Results : The effect of four weeks of functional balance training was found to be positive for dynamic postural control with statistically significant differences (P < 0.05). The increased strength of the muscles of the ankle dorsiflexors, the ankle plantar flexors, the foot invertors, and the foot evertors from the first to fourth weeks were also significant (P < 0.05). Conclusion : Four weeks of functional balance training resulted in improved dynamic postural control in those wearing high-heeled shoes. Functional balance training also improved the strength of the ankle muscles. This training may help prevent slipping and ankle sprains in people who wear high heels.